Limited Failure Censored Life Test Sampling Plan: Pareto-Rayleigh Model - Prasad, G; Subba Rao, R; R.L. Kantam, R (International Journal of Engineering and Technology, 2018)
A combination of Pareto and Rayleigh distributions considered for a new T-X probability model named as Pareto-Rayleigh distribution (PR distribution). We have chosen a life time random variable X from PR distribution whose lots are to be decided for acceptance or otherwise based on sample lifetimes drawn from the lot.Â A sampling scheme is developed in such way that the sample is divided into different groups and experiment is terminated whenever the first failure noticed in each group.Â The theory of ordered statistics is applied for the criterion of acceptance and is compared with the similar works proposed by other authors.Â Â